Motors of influenza vaccination uptake and vaccination advocacy in healthcare workers: Development and validation of two short scales. Issue 44 (22nd October 2018) - Vallée-Tourangeau, Gaëlle; Promberger, Marianne; Moon, Karis; Wheelock, Ana; Sirota, Miroslav; Norton, Christine; Sevdalis, Nick
Abstract: Healthcare workers (HCWs) are an important priority group for vaccination against influenza, yet, flu vaccine uptake remains low among them. Psychosocial studies of HCWs' decisions to get vaccinated have commonly drawn on subjective expected utility models to assess predictors of vaccination, assuming HCWs' choices result from a rational information-weighing process. By contrast, we recast those decisions as a commitment to vaccination and we aimed to understand why HCWs may want to (rather than believe they need to) get vaccinated against the flu. This article outlines the development and validation of a 9-item measure of cognitive empowerment towards flu vaccination (MoVac-flu scale) and an 11-item measure of cognitive empowerment towards vaccination advocacy. Both scales were administered to 784 frontline NHS HCWs with direct patient contact between June 2014 and July 2015. The scales exhibited excellent reliability and a clear unidimensional factor structure. An examination of the nomological network of the cognitive empowerment construct in relation to HCWs' vaccination against the flu revealed that this construct was distinct from traditional measures of risk perception and the strongest predictor of HCWs' decisions to vaccinate. Similarly, cognitive empowerment in relation to vaccination advocacy was a strong predictor of HCWs' engagement with vaccination advocacy. These findings suggest that the cognitive empowerment construct has important implications for advancing our understanding of HCWs' decisions to vaccinate as well as their advocacy behavior.